Macrozoobentos Composition In The Babura River Sumatra Utara - Masdiana Sinambela; Andreas Simorangkir; Frends Silaban (International Journal of Science and Environment (IJSE), 2024)
To determine the composition of macrozoobenthos in the waters of the Babura river. The parameters measured are biological parameters, namely macrozoobenthos composition supported by physical and chemical parameters in the Babura river waters. The parameters measured in this research are biotic parameters, namely the type of macrozoobenthos and abiotic parameters, namely physical and chemical parameters. Physical parameters such as: temperature, turbidity, and chemical parameters such as: pH (degree of acidity), (DO), BOD, COD, and phosphate. Taking macrozoobenthos in shallow water using a quadrant and in deep water using an Eckman grab. Physical/chemical parameters are measured in situ and ex situ. Ex-situ is carried out in the BTKL laboratory. This type of research is ex-post de facto or only reveals existing data. Macrozoobenthos composition found in the Babura river: 1. There are six species of insects, namely Chironomus sp, Aeshna grandis, Dragonfiy nymph macronia, Agrion sp, Damsefly nymph, Dragonfly; 2. There are eight species of gastropods, namely: Thiara winteri, Thiara sp, Melanoides tuberculata, Melanoides rustica, Melanoides gramnifera, Brotia testudinaria, , Planorbis sp, Lymnaea rubiginosa; 3. There are two species of Hirudinea/Clitellata, namely Leeches and Glossiphoniidae; 4 There is one species of trematode, namely Pomatiopsis lapidaria Say; 5. There is one species of crustacean, namely Gammarus sp; 6. There is one species of nematode, namely the rolled worm; 7. There is one species of Oligochaeta, namely Tubifex sp; 8. There are three species of Turbilaria, namely Planaria sp, Dugesia sp, Mesostoma sp, so the macrozoobenthos composition consists of 8 classes with a total of 23 species. Physical/chemical parameters still support macrozoobenthos life in the waters of the Babura river.